STRATEGI OPTIMALISASI PENERIMAAN PAJAK DAERAH PADA BADAN PENDAPATAN KOTA DENPASAR - Ni Luh Evayani; Putri Anggreni; Sebastianus Bambang Dwianto; Ni Luh Indiani; Ni Made Widiani; I Nyoman Wirakusuma (Forum Manajemen STIMI Handayani Denpasar, 2022)
Development is a series of activities or efforts to change the state of a country. Basically, national development aims to create a just and prosperous society through improving people's living standards. Regional taxes are one of the important components in Regional Original Income, namely mandatory contributions that can be imposed on everyone (taxpayers) without exception and the tax proceeds are used to finance the implementation of regional government and regional development. The purpose of this study was to determine the Strategy for Optimizing Regional Tax Revenue at the Denpasar City Regional Revenue Agency. The analytical techniques used to analyze the data are descriptive, qualitative, and SWOT analysis techniques. Where the results of the analysis show that the Denpasar City Revenue Agency has a good ability to respond to various threats and opportunities contained in its internal and external environment with the final value of the IFAS matrix of 3.37 and the final value of the EFAS matrix of 3.19. Being in Quadrant I is an aggressive strategy in a good position to have opportunities and strengths, so they can take advantage of existing opportunities. Through the use of the SWOT matrix, the strategies used in this research are Improving the Local Tax Intensification and Extensification Program, the Quality of Human Resources of the Regional Tax Apparatus, and Building Cooperation with Government, Private and Community Agencies in the collection of Regional Taxes at the Denpasar City Regional Revenue Agency.